Condom sterility in periprosthetic joint infection management at Universitas academic hospital in Bloemfontein 2018 - Tyumre, Ntsikelelo (University of the Free State, 2020)
Joint replacement surgery, especially of the hip and knee, is one of the most rewarding operations for both the patient and the orthopaedic surgeon worldwide. Hip replacement has been dubbed the operation of the century. This is because these replacements improve the quality of life for the elderly population crippled with arthritis, and in recent years, due to better implants, also improves quality of life in the younger generation presenting with joint problems. It is, however, not without complications, the most important being periprosthetic joint infections. Other complications include aseptic loosening, periprosthetic fractures and dislocation. Periprosthetic joint infection is the most dreaded of the complications because of its difficulty to manage and association with significant morbidity and bone loss. We therefore began by describing and defining periprosthetic joint infection and investigated the current epidemiological data available. We have reviewed literature and looked at the diagnostic criteria from the different societies and meetings from around the world. Parvizi et al. developed an algorithm and proposed criteria that are based on the latest data and tests. This is explained in detail in the first chapter of this dissertation. The management of periprosthetic joint infection is dependent on the amount of time from the index joint surgery. An outline of the deferent management options are presented, while bearing in mind that two-stage revision surgery is the gold standard of management. Management of periprosthetic joint infection is associated with bone loss, either with the removal of infected implants or removal of the cement spacer in the second surgery of the twostage procedure. A recent unpublished study done locally in our department showed that putting a cement spacer in a condom and then placing the condom-cement spacer in the joint to allow it to set, and then taking out the condom-cement spacer after the cement had set, was associated with no bone loss. The study also showed that female condoms were stronger and more durable compared to the male condoms. The question that needed to be addressed, was whether it is safe to introduce condoms into the joint? Based on the literature, there is a 10% chance that condoms maybe contaminated. We investigated the sterility of condoms from the packaging and how to improve the sterility of the condoms. Sixty government-issued female condoms were used for the study, of which 30 were tested straight from the packaging and the other 30 were first put through hydrogen peroxide gas plasma sterilisation and then tested by means of MC&S. Similar to previously published studies, contamination of the condoms was confirmed, although in our study, the rate of contamination was 60%. We also isolated nonvirulent environmental and implant contaminants. The most important aspect of the results was that we were able to achieve 100% sterility of the condoms with hydrogen peroxide gas plasma. This was significant because we can place condoms for its intended use in the joints without introducing further infection in the joint. Once sterilised, condoms can also be used for other sterile/aseptic medical procedures, such as ultrasound probe covering and temperature probe covers.
Keywords: Dissertation (M.Med. (Orthopaedic Surgery)--Univesity of the Free State, 2020; Joint replacement surgery; Periprosthetic joint infections; Management of periprosthetic joint infection; Condom-cement spacer